MENAKAR KEARIFAN AGAMA DENGAN BUDAYA MEASURING RELIGION WISDOM BY CULTURE - Sudrajat, Unggul (Puslitjakdikbud Balitbang Kemdikbud, 2016)
AbstractThe object of the research is in Rembang, Central Java. It is related to the conflictof Sapta Darma faith. beliefs is the mistical human admission . Meanings of religionshould be understood as part of the knowledge. This research is motivated by researcher’sdesire to reveal the roots of the problem which lead to the conflict between religions orbeliefs that often occurs in the community. The main issue of this study is focused onhow the actions of the government and religious leaders that have authorities to solve theproblems. The purpose of this study is to find the problem roots that lead to the actualissues of belief in society. This study is included into the field research with the object ofconflict is Sapta Darma belief in Rembang by using descriptive-analytic point of view.the Sources of the data used in the study are interview, documents, and field observations.This research uses an anthropological approach. Based on the research results, the caseof incendiarism in Blando Hamlet, Plawangan Village, Kragan District in Rembang hassocial conflicts that is caused by reliance. the conflict does not necessarily have to endwith the burning, but there are many other solutions that can be used as a unifying one ofthem is by a dialogue. By using a dialogue the conflict can be minimized. AbstrakObjek penelitian ini di Rembang, Jawa Tengah terkait dengan konflik kepercayaanSapta Darma. Kepercayaan merupakan pengakuan manusia terhadap sesuatu yang gaib.Pemaknaan terhadap agama harus dipahami sebagai bagian dari pengetahuan bahwa agamasebagai ilmu. Penelitian ini dilatarbelakangi keinginan peneliti untuk mengungkapkanakar permasalahan yang mengakibatkan adanya konflik antar agama atau kepercayaanyang kerap terjadi di masyarakat. Pokok pembahasan dalam penelitian ini terfokus padabagaimana tindakan pemerintah dan tokoh agama yang berwenang menyikapi persoalanpersoalankepercayaan. Tujuan dari penelitian ini menemukan akar permasalahan yangmengakibatkan adanya isu-isu aktual kepercayaan yang terjadi di masyarakat. Penelitianini termasuk penelitian lapangan dengan objek konflik kepercayaan Sapta Darma diRembang dengan sudut pandang deskriptif-analisis. Sumber data yang digunakan dalampenelitian wawancara, dokumen-dokumen, dan observasi dilapangan. Penelitian inimenggunakan pendekatan antropologis. Berdasarkan hasil penelitian, kasus pembakaranrumah ibadah di Dukuh Blando, Desa Plawangan, Kecamatan Kragan di Rembangtelah terjadi konflik sosial yang diakibatkan aliran kepercayaan. Konflik ini tidak sertamertaharus berakhir dengan pembakaran, akan tetapi masih banyak solusi lain yang bisadijadikan pemersatu salah satunya adalah dialog, sebab dengan berdialog konflik pun bisadiminimalisir.